Hydroethanolic Extract of Solanum paniculatum L. Fruits Modulates ROS and Cytokine in Human Cell Lines - Ferraz, Ana Paula C. R. [UNESP]; Sussulini, Alessandra; Garcia, Jéssica L. [UNESP]; Costa, Mariane R. [UNESP]; Francisqueti-Ferron, Fabiane V. [UNESP]; Ferron, Artur J. T. [UNESP]; Silva, Carol Cristina V. De A. [UNESP]; Corrente, José Eduardo [UNESP]; Manfio, Vanessa M. [UNESP]; Namba, Vickeline [UNESP]; Lima, Giuseppina P. P. [UNESP]; Pereira, Bismarque S. [UNESP]; et al. (Hindawi, 2020)
Solanum paniculatum L. or popularly known as jurubeba is an herbal medicinal plant. A few studies have investigated its biological effects; however, research aimed at elucidating the redox balance effects from its fruits has not been reported so far. ROS interplays in various fields of medicine such as chemotherapy. Here, we evaluated antioxidant and inflammatory activities of the hydroethanolic extract of Solanum Paniculatum L. (HESPL) fruits in breast cancer cells, as well as its phytochemical profile. The antioxidant profile (carotenoids and phenolic compounds) was obtained by HPLC-DAD-UV and HPLC-APCI-MS. Cancer cell lines and human vein endothelial cells (HUVECs) were cultivated and treated with 1.87-30 μg/mL of HESPL for 24 hrs. Cytotoxicity, oxidative, and inflammation biomarkers were evaluated. The dose of 30 μg/mL of the HESPL extract presented cytotoxicity in the MCF-7 cell line. However, for MDA-MB-231, the cytotoxicity was observed in the dose of 1.87 g/mL. The 1.87 μg/mL and 3.75 μg/mL doses decreased the concentration of IL-6 in MCF-7 cells. In the MDA-MB-231 cells, the HESPL did not decrease the IL-6 concentration; however, in the doses of 15 and 30 μg/mL, an increase in this parameter was observed. The HESPL increased IL-1β concentration in HUVECs. The ROS level in MCF-7 was elevated only at the 30 μg/ml dose. Regarding MDA-MB-231, HESPL promoted increased ROS levels at all doses tested. HUVEC showed no increase in ROS under any dose. HESPL treatment may modulate cytotoxicity, ROS, and cytokine levels due to its phytochemical profile, and it has shown an antioxidant or anti-inflammatory effect.